(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Semantic web facilitates the use of automated processing of descriptions on the web and exchange and representation of information is done in a meaningful way. But a conventional search engine, the context and semantics of the user query is not analyzed fully and the data is not well structured so it does not provide the relevant content needed by the user. Hence to overcome this problem, semantic web search has become an essential part in todayâ€™s world. In this proposed method the user given query is analyzed semantically and the web data is stored in an ontology which is well structured and conventional search is performed using SPARQL query viewer plug-in. Finally, ranking algorithm is used to rank the extracted links for the given query.Â The results obtained are accurate enough to satisfy the request made by the user. The level of accuracy is enhanced since the ontology is made consistent and query is analyzed semantically to retrieve the correct result. The domain specific evaluation time obtained shows promising results.